Application of Biogas with Fermenting Bacteria from Manure Raw Material on Stoves and Generators - Rudy Yulianto; Sukardi Sukardi; Meika Syahbana Rusli; Sari Sekar Ningrum (Universitas Panji Sakti, 2023)
The raw biogas from the digester is a gas produced by bacterial fermentation which has a composition of methane (CH4), carbon dioxide (CO2), hydrogen sulfide (H2S), water vapor, and various other gases. Gases other than methane in raw biogas can damage the combustion system if used directly. The digester that produces biogas is used to move the generator engine using raw materials, such as cow feces, goat feces, fowl feces, straw, husks, and clean water. In the mixing process, all the raw materials are stirred or mixed evenly in the digester. Next is the process with five stages, namely (1). In the first stage: on the 11th day, adding clean water and fermentation carried out for 21 days, (2). The second stage: adding starter, hormones, charcoal flour, cow feces, fowl fees, goat feces, straw, and husks, then fermented for 7 days. (3). The third stage: adding a starter and fermenting it for 7 days. (4). Fourth stage: ready-to-use compost or solid fertilizer is ready to produce. (5). Fifth stage: liquid fertilizer is ready for production. In the gathering stage: all raw materials are stirred or mixed evenly in the digester and fermented for 1.5 months to become biogas. The last stage is the distribution of biogas: for household needs, and generators. From this research, it can conclude that the water column height (h) is 10.42 cm, and the maximum water column height is 9 cm so that the reactor is safe and the maximum pressure that can be attained is 879.1918 kg.m-1.s-2. The heating rate for ratio A is 0.0600 oC.s-1 and the heating rate for ratio B is 0.0640 oC.s-1. The calorific value produced from heating 1 liter of clean water using biogas from ratio A is 297.99315 kJ, and the calorific value of ratio B is 288.9174 kJ. With a compressor pressure of 8 psi, biogas can be inserted in this using a freon tube for a maximum of 6000 seconds with a mass of 6163 grams. In filling biogas, the biogas manometer should show the maximum number (between 16.50 – 25.50).